Adenosine, bridging chronic inflammation and tumor growth - Chen, Luxia; Alabdullah, Mohamad; Mahnke, Karsten (Frontiers in Immunology, 2023)
Adenosine (Ado) is a well-known immunosuppressive agent that may be released or generated extracellularly by cells, via degrading ATP by the sequential actions of the ectonucleotides CD39 and CD73. During inflammation Ado is produced by leukocytes and tissue cells by different means to initiate the healing phase. Ado downregulates the activation and the effector functions of different leukocyte (sub-) populations and stimulates proliferation of fibroblasts for re-establishment of intact tissues. Therefore, the anti-inflammatory actions of Ado are already intrinsically triggered during each episode of inflammation. These tissue-regenerating and inflammation-tempering purposes of Ado can become counterproductive. In chronic inflammation, it is possible that Ado-driven anti-inflammatory actions sustain the inflammation and prevent the final clearance of the tissues from possible pathogens. These chronic infections are characterized by increased tissue damage, remodeling and accumulating DNA damage, and are thus prone for tumor formation. Developing tumors may further enhance immunosuppressive actions by producing Ado by themselves, or by “hijacking” CD39+/CD73+ cells that had already developed during chronic inflammation. This review describes different and mostly convergent mechanisms of how Ado-induced immune suppression, initially induced in inflammation, can lead to tumor formation and outgrowth.